Uncertainty, Contrariness and the Double-Bind: Middle Managers' Reactions to their Changing Contracts - Dopson, S; Neumann, J (1998)
This article describes the emerging changes in psychological contracts being experienced by British middle managers in relation to their employing organizations, the middle managers' negative reactions to these changes and organizational responses to such negativity. By analysing case studies of 16 organizations, a classification of changes to five elements of the psychological contract are identified: knowledge, motivation, goals and means, role behaviour and ethics. By analysing the semi-structured interviews of 37 middle managers, selected from a much larger database for their obvious negative reactions, a continuum of such reactions is considered: uncertainty, contrariness and double-bind. This consideration leads, then, to suggestions for further research.